PEMBENTUKAN DAN FASILITASI KAMPUNG KB WARU KIDUL KABUPATEN PEKALONGAN Tema : Membentuk Bina Keluarga Balita Holistik Integratif (BKB, Posyandu dan PAUD) di Kampung Kb Waru Kidul Kabupaten Pekalongan - Yuniarti Yuniarti; Devi Ria Hardini; Madinatul Fitriana; Adi Setiawan (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2021)
Under five years family development is  community based health efforts managed by health facilitators which are community based. Under five years family development could be integrated with others programs for achieving higher outcomes and benefits. The forms of integration is holistic-integrative under five years family development (BKB-HI), its integration between under five years family development and integrated services post. Integration also between under five years family development and early education or both of them. Base on problems mapping in Waru Kidul Family Planning village of Pekalongan regency in November 19th 2018 known that BKB’s situation are about : not integrated with integrated services post, nor with early education for children. Health facilitators are not giving education about growth and development of children. That are caused health facilitators unskilled well about growth and development steps of children. Identification and problem mapping by observing BKB’s activities which are interviewing four facilitators and twenty children’s mothers. The questions are about growth and development of children under five years, and also about educational game toys. Some of facilitators have good knowing about growth and development steps of children, but they are not good of knowing about educational game toys for maximizing childres’s development. Interview with children’s mother about stimulation for maximizing growth and development of children under five years old. During accompaniment of BKB, its integrated with integrated services post and early education for children (PAUD Uswatun Khasanah). Health education about child growth and development stimulation was carried out on November 30 2018, attended by BKB-HI facilitators, early education school teachers and parents. After educating, parents' knowledge about growth and development is getting better, facilitators and teachers can optimize educational props to stimulate child growth and development.Keywords : Holistic integrative, growth development, under five years child